KOMPLEKSITAS TUGAS, KEAHLIAN AUDIT DAN TEKANAN KETAATAN PENGARUHNYA TERHADAP AUDIT JUDGMENT - Trisnaningsih, Sri (Journal of Accounting and Strategic Finance, 2010)
The aim of this research to analysis empirically how far influence of adherence pressure, duty complexity and expertise of audit to audit judgement. The object of this research to use 42 Office of Public Accountant in Surabaya. While source of used data from answer of qoesioner disseminated at 30 respondent. The analysis by multiple regression and using program of SPSS. 16.0 For Windows The result of analysis can be concluded that first hypothesis  expressing that adherence pressure, duty complexity, and expertise of audit significantly influence to audit judgement and second hypothesis expressing that duty complexity have an effect on most dominant to audit judgement   Keywords : Pressure Adherence, Complexity Duty, Membership of Audit, and Audit Judgment.